2003
DOI: 10.1007/bf03043092
|View full text |Cite
|
Sign up to set email alerts
|

The cornucopia of chilly winters: Ocean quahog (Arctica islandica L., Mollusca) master chronology reveals bottom water nutrient enrichment during colder winters (North Sea)

Abstract: The cornucopia of chilly winters: Ocean quahog (Arctica islandica L., Mollusca) master chronology reveals bottom water nutrient enrichment during colder winters (North Sea). -Senckenbergiana marit., 32 (1/2): 165-175, 6 figs., 1 tab.; Frankfurt a.M.]We studied variations in annual shell growth rates of ten live-collected Arctica islandica specimens from three localities at the Dogger Bank in the central North Sea. Synchronous growth curves from contemporaneous specimens enabled the construction of a 65-year mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
(26 reference statements)
1
12
0
Order By: Relevance
“…Furthermore, hypoxic conditions associated with high summer temperatures in the Oyster Grounds (de Wilde et al 1984) could lead to a reduction of shell growth rates, because the animals become dormant (Abele 2002). The weak positive relation between growth and temperature in spring and summer, and the stronger negative relation with autumn and winter temperatures, are consistent with the results of Schöne et al (2003Schöne et al ( , 2004, who found a significant negative correlation between winter air temperature and shell growth in A. islandica from the Dogger Bank (central North Sea). Schöne et al (2004) showed that increment width in A. islandica shells from the Amrum Bank did not correlate with stable isotope derived temperatures in the main growing season (February to September).…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, hypoxic conditions associated with high summer temperatures in the Oyster Grounds (de Wilde et al 1984) could lead to a reduction of shell growth rates, because the animals become dormant (Abele 2002). The weak positive relation between growth and temperature in spring and summer, and the stronger negative relation with autumn and winter temperatures, are consistent with the results of Schöne et al (2003Schöne et al ( , 2004, who found a significant negative correlation between winter air temperature and shell growth in A. islandica from the Dogger Bank (central North Sea). Schöne et al (2004) showed that increment width in A. islandica shells from the Amrum Bank did not correlate with stable isotope derived temperatures in the main growing season (February to September).…”
Section: Discussionsupporting
confidence: 78%
“…Climate affects the marine ecosystems indirectly by changing the ecosystem properties that are of importance to the growth of organisms (Ottersen et al, 2001(Ottersen et al, , 2004; significant aquatic properties for the growth of marine organisms include temperature, salinity, food supply, water column stratification and sedimentation (Schö ne et al, 2003a;Witbaard et al, 2003). Growth may be influenced contemporaneously or with lagged responses (Witbaard et al, 2003;Ottersen et al, 2001Ottersen et al, , 2004.…”
Section: Influence Of North Atlantic Oscillation (Nao)mentioning
confidence: 99%
“…Another example is the bivalve Arctica islandica. The growth rings of its shell are a good index for climatic events, impressively demonstrated by Schöne et al (2003Schöne et al ( , 2005. Additionally, the shell of A. islandica together with the shells of Mya truncata and Chamelea striatula can be used to show sediment re-suspension strength due to storms, as shown by Witbaard et al (2005).…”
Section: Low Winter Temperaturesmentioning
confidence: 95%